EFFECTS OF WATER STRESS ON THE UPTAKE OF NUTRIENTS BY BEAN SEEDLINGS (Phaseolus vulgaris L.) - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2011)
The influence of two levels of water stress on Phaseolus vulgaris L. plants was investigated in pot experiments conducted under growth room conditions. The results revealed that increased water stress caused adverse effects on plant growth and development. Various measured parameters of both fresh- and dry-matter production were significantly affected at severe water stress, with the exception of root dry weight. Flame photometry (FP) and inductively coupled plasma atomic emission spectrometry (ICP-AES) analyses of leaf nutrients indicated that the concentration of K+ was higher than that of all other nutrients. The concentrations of K+ and Mg2+ were significantly decreased under severe stress (S2) treatments. Zn2+ and Mn2+ content increased in the leaves of both moderate (S1) and severe (S2) stressed plants, while Ca2+ and Fe3+ decreased under severe stressed leaves compared to control values. Na+ content of leaves was measured, but in all cases was below the limits of detection.
Keywords: Water stress; bean; Phaseolus vulgaris L.; nutrients; SOIL SOLUTION COMPOSITION; CELL-MEMBRANE STABILITY; DROUGHT STRESS; PHOSPHORUS-NUTRITION; POTASSIUM NUTRITION; ZINC ADSORPTION; PLANT-RESPONSES; USE EFFICIENCY; PEARL-MILLET; GROWTH